2000
DOI: 10.1111/j.1574-695x.2000.tb01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of human keratinocytes after bacterial invasion

Abstract: In this study, we examined the invasive capacity of Staphylococcus aureus and Salmonella typhi in human keratinocytes and monitored the number of viable intracellular bacteria at different post-infection times. The strains tested entered keratinocytes; both S. typhi and S. aureus were internalized within 30 min to 2 h after infection. No intracellular multiplication was observed, but S. typhi and S. aureus remained viable 72 h after infection. We also demonstrated that keratinocyte death following S. typhi and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 32 publications
0
39
1
Order By: Relevance
“…While S. aureus is not generally considered an intracellular pathogen, many host cells, including corneal epithelial cells, internalize S. aureus (19). Furthermore, internalization of S. aureus can induce apoptosis in many cell types, including epithelial cells, endothelial cells, and keratinoyctes (3,20,29,35). If retinal cells internalize S. aureus, bacterial toxins and the proteases could be released through pores in a phagocytic vacuole, potentially making the cell more vulnerable to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…While S. aureus is not generally considered an intracellular pathogen, many host cells, including corneal epithelial cells, internalize S. aureus (19). Furthermore, internalization of S. aureus can induce apoptosis in many cell types, including epithelial cells, endothelial cells, and keratinoyctes (3,20,29,35). If retinal cells internalize S. aureus, bacterial toxins and the proteases could be released through pores in a phagocytic vacuole, potentially making the cell more vulnerable to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In epithelial cells, keratinocytes, or osteoblasts, S. aureus-induced apoptosis may require internalization of the bacteria (26,27,30,32,33). Conversely, Bantel et al (16) showed that S. aureus α-toxin does not require bacterial internalization to induce apoptosis.…”
Section: Figurementioning
confidence: 99%
“…Similarly, internalization has been reported to be a prerequisite for inducing apoptosis in cells infected with Staphylococcus aureus (Nuzzo et al, 2000;Kahl et al, 2000;Menzies & Kourteva, 1998;Bayles et al, 1998), suggesting that the induction of programmed cell death by facultative intracellular bacteria is a common occurrence in host cellbacterium interactions. Tsai et al (1999) reported that 11-13 % of HEp-2 cells showed indications of apoptosis at 20 h following GAS infection, and that about 40 % of the cells exhibited membrane injury.…”
Section: Hep-2 Cell Damage Is Caused By Programmed Cell Deathmentioning
confidence: 99%